Gender equality and social inclusion in agribusiness ecosystems for multidimensional mapping of opportunities and challenges: Workshop report - Adam, Rahma; Waithanji, Elizabeth M.; Gatonye, Margaret; Muiruri, Esther; Njogu, Lucy; Mawia, Harriet; Njoki, Irene; Wanjera, Mary (Diversification for resilient agribusiness ecosystems in East and Southern Africa (ESA) Initiative, 2022)
Agribusiness in Kenya has been growing tremendously as more people continue to realize its benefits. It is mainly driven by the abundant natural resources readily available in Kenya. Agribusiness has created employment opportunities for women and youth who are locked outside formal employment. Which leads to the question: are agribusiness opportunities equitably distributed in terms of gender and social inclusion?